Knowledge of Students Regarding Complementary Feeding (MP-ASI) for Infants Aged 6–24 Months - INDAH AZHARI (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: The period of infancy between 6–24 months of age is a critical stage in the life cycle that significantly influences children’s growth and development. At six months of age, infants have increased energy and nutrient requirements, making breast milk alone insufficient to meet their nutritional needs. Therefore, the introduction of appropriate complementary feeding is essential and should follow recommended guidelines by considering factors such as age suitability, portion size, feeding frequency, food texture, dietary diversity, and food safety. Adequate knowledge regarding complementary feeding practices is an important competency that nursing students, as future healthcare professionals, should possess, particularly in their role as health educators in providing health education and promoting appropriate infant feeding practices within the community. Objective: This study aimed to describe the level of knowledge among students regarding appropriate complementary feeding practices for infants aged 6–24 months. Methods: This study employed a descriptive research design. The study population consisted of all fourth-semester Diploma III Nursing students, totaling 152 students. A sample of 122 respondents was determined using the Slovin formula and selected through a non-probability sampling technique using purposive sampling. Data were collected using informed consent forms and a structured questionnaire distributed via Google Forms. The data were analyzed descriptively using IBM SPSS Statistics and presented as frequency distributions and percentages. Results: Most respondents were 20 years old (80 respondents; 65.6%), the majority were female (113 respondents; 92.6%), and all respondents were Diploma III Nursing students (122 respondents; 100%). Regarding the level of knowledge of complementary feeding, most respondents had good knowledge (80 respondents; 65.6%), followed by sufficient knowledge (38 respondents; 31.1%) and poor knowledge (4 respondents; 3.3%). Conclusion: Most Diploma III Nursing students demonstrated a good level of knowledge regarding complementary feeding for infants aged 6–24 months. These findings indicate that the students have an adequate understanding of recommended complementary feeding practices. However, continuous educational reinforcement and practical learning experiences are still needed to further enhance their competence as future healthcare professionals.